The impact of Hofstede's national culture on usage of emails among academician in Malaysian public universities - Bali Mahomed, Anuar Shah; Mcgrath, Michael G.; Bong, Zhi Yuh (Science Publishing Corporation, 2018)
This research investigates the impact of Hoftstede’s National Culture which mediated by the Technology Acceptance Model (TAM) on usage of emails among academician in Malaysian public universities. Data was collected by using survey questionnaires among 146 academic staff from two public universities in Malaysia. Path analysis was conducted using SmartPLS 2.0 to assess the usage of emails model. Study found that power distance (PD), uncertainty avoidance (UA) and collectivism (C) have negative impact on perceived ease of use (PEOU) of usage of emails. Study further discovered that PD, and C have negative influence on perceived usefulness (PU) of usage of emails. In addition, study found that masculinity (M) has no noteworthy impact on both PEOU and PU of usage of emails. Moreover, long-term orientation (LT) and Indulgence (I) were found to have noteworthy positive relationship with PEOU and PU on usage of emails. On technology acceptance model (TAM), PEOU and PU were found to have noteworthy positive impact on usage of emails (U) while PEOU has a noteworthy positive impact PU of usage of emails. This paper discusses the implications of these findings for future academic research and practice.